2018
DOI: 10.1126/science.aar2663
|View full text |Cite
|
Sign up to set email alerts
|

NUFIP1 is a ribosome receptor for starvation-induced ribophagy

Abstract: The lysosome degrades and recycles macromolecules, signals to the master growth regulator mTORC1 [mechanistic target of rapamycin (mTOR) complex 1], and is associated with human disease. We performed quantitative proteomic analyses of rapidly isolated lysosomes and found that nutrient levels and mTOR dynamically modulate the lysosomal proteome. Upon mTORC1 inhibition, NUFIP1 (nuclear fragile X mental retardation-interacting protein 1) redistributes from the nucleus to autophagosomes and lysosomes. Upon these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
283
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 302 publications
(296 citation statements)
references
References 53 publications
13
283
0
Order By: Relevance
“…Therefore, we introduced a measure of charge conservation (see Methods) that specifically accounts for the local presence of positively charged amino acids in an alignment. Recent studies have shown enrichment of positively charged amino acids in ribosomal proteins [32]. Upon computing the charge score for our sequence alignments, we indeed found some significant correlation between the sequence conservation and charge conservation scores for bacterial proteins with Pearson's correlation r 2 = 0.70, 0.51 and 0.47 (p-values < 10 −4 ) for bacterial alignments of uL4, uL23 and uL22, respectively (see Supplementary Data).…”
Section: Conservation Of Ribosomal Protein Sequence and Positive Charsupporting
confidence: 52%
“…Therefore, we introduced a measure of charge conservation (see Methods) that specifically accounts for the local presence of positively charged amino acids in an alignment. Recent studies have shown enrichment of positively charged amino acids in ribosomal proteins [32]. Upon computing the charge score for our sequence alignments, we indeed found some significant correlation between the sequence conservation and charge conservation scores for bacterial proteins with Pearson's correlation r 2 = 0.70, 0.51 and 0.47 (p-values < 10 −4 ) for bacterial alignments of uL4, uL23 and uL22, respectively (see Supplementary Data).…”
Section: Conservation Of Ribosomal Protein Sequence and Positive Charsupporting
confidence: 52%
“…Multimodal analysis of mitochondria from specific cell types will be important for trying to dissect mitochondrial heterogeneity in complex tissues, such as the brain and kidney. Furthermore, the ability to rapidly isolate mitochondria from specific cell-types without the need for cell sorting and long centrifugation steps can reduce the magnitude of distortion of the original mitochondrial state, as well as significantly decrease the time and effort needed to acquire the desired mitochondrial material, which can be useful for not just metabolomic but also proteomic work by better preserving the native proteomic mitochondrial profile and the interactions of proteins that peripherally associate with mitochondrial membranes (22). Of note, the design of our in vivo workflow is such that it can also be combined with other downstream studies aside from those utilized here, such as genomic and transcriptomic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…At a more global level, our study shows how protein levels can be more or less robust against changes in the ribosomal pool, which can simultaneously affect all initiation rates in a cell. Since the level of ribosomes present in a cell fluctuates over time [29], it would be interesting to see if protein levels scale uniformly with these variations across genes, and if not, whether the differences in λ 0 can explain it.…”
Section: Discussionmentioning
confidence: 99%